Decreased expression of FOXA2 promotes eutopic endometrial cell proliferation and migration in patients with endometriosis. Issue 2 (February 2018) - Lin, Anping; Yin, Juan; Cheng, Chao; Yang, Zhu; Yang, Huan
Abstract: Endometriosis is characterized by eutopic endometrial cell 'metastasis' to ectopic foci. FOXA2 is a member of the forkhead transcription factor family, which may participate in transcriptional regulation in endometrial cells and contribute to the aetiology of endometriosis. This study investigated the roles played by FOXA2 in eutopic endometrium using endometriosis samples. Western blotting showed that the relative expression of FOXA2 was significantly reduced in eutopic endometrium from patients with endometriosis ( n = 14) compared with endometriosis-free controls ( n = 16) (0.69 ± 0.07 versus 1.24 ± 0.06, P < 0.05). To mimic eutopic endometrium of endometriosis, primary eutopic endometrial stromal cells (ESC) of controls were harvested and transfected with FOXA2 siRNA. MTT assay showed that cell viability of ESC with transfected FOXA2 siRNA increased significantly, whereas the apoptosis rate decreased as indicated by flow cytometry experiments (both P < 0.05). Wound healing assays revealed that transfection of FOXA2 siRNA promoted ESC migration. Moreover, real-time PCR analysis showed progesterone-induced FOXA2 expression in ESC under physiological conditions. In conclusion, these findings indicate that FOXA2 might be a progesterone-induced gene, which may participate in the 'metastatic' process of eutopic endometrium to ectopic loci in patients with endometriosis.